A-Subclass ATP-Binding Cassette Proteins in Brain Lipid Homeostasis and Neurodegeneration - Piehler, Armin P.; Özçürümez, Mustafa; Kaminski, Wolfgang E. (Frontiers in Psychiatry, 2012)
The A-subclass of ATP-binding cassette (ABC) transporters comprises twelve structurally related members of the evolutionarily highly conserved superfamily of ABC transporters. ABCA transporters represent a subgroup of “full-size” multispan transporters of which several members have been shown to mediate the transport of a variety of physiologic lipid compounds across membrane barriers. The importance of ABCA transporters in human disease is documented by the observations that so far four members of this protein family (ABCA1, ABCA3, ABCA4, ABCA12) have been causatively linked to monogenetic disorders including familial high-density lipoprotein (HDL) deficiency, neonatal surfactant deficiency, degenerative retinopathies and congenital keratinization disorders. Recent research also point to a significant contribution of several A-subfamily ABC transporters to neurodegenerative diseases, in particular Alzheimer’s disease. This review will give a summary of our current knowledge of the A-subclass of ABC transporters with a special focus on brain lipid homeostasis and their involvement in Alzheimer’s disease.